Application of situational simulation based on the Mini-CEX and DOPS rating scales in urology clinical training - Xu, Ben; Zhang, Jia-en; Ye, Lin; Yuan, Chang-wei (Frontiers in Medicine, 2024)
Objective The objective of the study was to investigate the application effect of scenario simulation teaching based on the Mini-Clinical Evaluation Exercise (Mini-CEX) and direct observation of procedural skills (DOPS) rating scales in urology clinical apprenticeship training. Materials and methods A total of 32 students from the class of 2015–2017 who completed their traineeship in the Department of Urology of our hospital were selected and divided into a research group and a routine group. Routine teaching was implemented for the trainees in the control group, while situational simulation teaching based on the Mini-CEX and DOPS scoring scales was implemented for the trainees in the research group. The Mini-CEX and DOPS scores and student satisfaction were compared at the time of admission and discharge between the two groups. Results At the time of admission, there was no statistically significant difference between the Mini-CEX and DOPS scores of the two groups of trainees (p > 0.05). However, at the time of discharge, the Mini-CEX and DOPS scores of the trainees in the study group were 53.21 ± 4.52 and 81.23 ± 3.57, respectively, which were significantly higher than those in the conventional group (p < 0.001), and the trainees in the study group’s satisfaction with teaching was (20.11 ± 2.31), which was significantly higher than that of the conventional group (p < 0.001). Conclusion Implementing scenario simulation teaching based on the Mini-CEX and DOPS rating scales in urology clinical traineeship can significantly improve trainees’ surgical skills while also leading to high levels of satisfaction with the teaching method.